(untitled) (The Pakistan Development Review, 1987)
Firm-level stochastic CES production functions are specified for large and Small-scale firms in twelve manufacturing industries in Pakistan. Assuming that firms within specified asset-size categories for which aggregative data are available have the same levels of productive inputs, the elasticities of substitution of labour for capital are estimated, using weighted least-squares regression. For large-scale firms, the estimated elasticities are generally not significantly different from one, whereas for small-scale firms the elasticities are significantly smaller than one but greater than zero. These results indicate that there may exist more possibilities for the substitution of labour for capital in manufacturing industries in Pakistan than were claimed by earlier researchers. This finding has important policy implications for Pakistan’s economic development.